Cross-leg flap after free flap failure: a case report - Azcue, Arsenio F. A.; Silva, Jorge L. L.; Riera , Ricardo F. (International Journal of Research in Medical Sciences, 2024)
The cross-leg flap is a technique that has been used for a long time to address defects in the distal third of the leg. Currently, the gold standard for these defects is free flap reconstruction. However, the success of microsurgery is not always guaranteed due to a wide range of extrinsic and intrinsic factors. In this study, we present the use of a cross-leg flap as an alternative in the case of free flap failure, performed in the plastic and reconstructive surgery department of the General Hospital of Mexico. The cross-leg flap represents a reliable, simple, and effective alternative when free flaps are not suitable or as a rescue in case of their failure, either due to extrinsic or patient-related causes.